On epi-convergence for set-valued maps. (1st February 2022) - Hernández, E.; López, R.
ABSTRACT: Epi-convergence plays an important role when studying the behaviour of a set optimization problem under variations of its data. In this paper, we obtain properties for this notion and compare it with other convergence notions for set-valued maps that have been used recently to study the stability of set optimization problems.